2007
DOI: 10.1149/1.2789247
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Electro-Reduction on C22 and C276 Nickel Metal Alloy

Abstract: The C22 and C276 alloy metal surfaces were characterized for electrochemical activity in alkaline aqueous media in the presence and absence of oxygen (O 2 ) and at 30° C. The metal was studied by electrochemical impedance spectroscopy (EIS), voltammetry with a still electrode and a specialized rotating ring-disk electrode (RRDE) technique, the cyclic potential ring measurement (CPRM) method (1). The CPRM method gave the steady state O 2 reduction kinetics. An initial study of O 2 reduction on gold yielded virt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…27 An electrochemical and corrosion study of Alloy C-22 in 0.5 M NaCl solution showed that open-circuit passivation of the alloy had a pronounced effect on the kinetic parameters of both the cathodic and anodic reactions involved in the corrosion process. 28 Both reactions were slower than those proceeding on the active (cathodically-reduced) alloy surface.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…27 An electrochemical and corrosion study of Alloy C-22 in 0.5 M NaCl solution showed that open-circuit passivation of the alloy had a pronounced effect on the kinetic parameters of both the cathodic and anodic reactions involved in the corrosion process. 28 Both reactions were slower than those proceeding on the active (cathodically-reduced) alloy surface.…”
mentioning
confidence: 99%
“…26 The O 2 reduction reaction on Alloys C-22 and C-276 in alkaline solutions appears to proceed via two 2-electron processes in series, with kinetic rate constants at 30 • C estimated to be in the range 0.001 to 0.232 cm/s, depending on the potential. 27 An electrochemical and corrosion study of Alloy C-22 in 0.5 M NaCl solution showed that open-circuit passivation of the alloy had a pronounced effect on the kinetic parameters of both the cathodic and anodic reactions involved in the corrosion process. 28 Both reactions were slower than those proceeding on the active (cathodically-reduced) alloy surface.…”
mentioning
confidence: 99%